PERILAKU COPY PASTE DALAM WHATSAPP GROUP PERTEMANAN: (Studi Etnografi Virtual Tentang Perilaku Copy Paste Dalam Whatsapp Group Pertemanan) - Rachmaniar; Susanti, Santi (Universitas Swadaya Gunung Jati, 2023)
The current existence of WhatsApp has become an unavoidable need. As a result, everyone has a lot of WAG and is busy with their respective posts. Anyone from us can post, or share anything in the WAG, including greetings of joy and sorrow, where the posts submitted are the same or different. For this reason, the authors are interested in understanding how the behaviour of copypaste appears in WAG friendship and what is often copied and pasted into WAG friendship. The method used in this study is a qualitative method with a virtual ethnographic approach to several WAG friendships. The results of this study indicate that: 1) copypaste behaviour of speech often occurs in large groups of WhatsApp groups, with participants of more than 40 people, and occurs in school alumni groups, or friends who have joined certain institutions or institutions; 2) the thing that is often in the copypaste of the WhatsApp group participants is great friendship is giving joyful and grief; 3) the copypaste behaviour of the greetings made by WhatsApp group participants is that big friendship is the one delivered 100 per cent the same, both from words, a series of sentences, the use of punctuation, to writing errors. Keywords: WhatsApp, copy-paste behaviour, virtual ethnography